An Epidemiological Study On The Parasite Cutaneous Leishmaniasis In Iraq - Sura Samer Alwan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Leishmaniasis is recognized as a significant health concern in Iraq. The disease begins with minor elevations (papules) and progresses into ulcers. Epidemiological investigations play a crucial role in managing and implementing effective preventive strategies for this disease. This study examines the epidemiology of cutaneous leishmaniasis in Iraq over the past 7 years. This descriptive-analytical cross-sectional inquiry analyzed data concerning patients with cutaneous leishmaniasis over the previous 7 years at the Iraq Health Center. Demographic and epidemiological data of the patients were collected from healthcare centers in Iraq through collaborative efforts with healthcare facilities. Using SPSS software, epidemiological records of the patients were extracted and subjected to statistical analysis employing the chi-square test. Out of 175 patients examined, 88 were male (53%), and 87 were female (47%). The majority of patients belonged to the age bracket of 9 months to 4 years, with the lowest number of cases in the age group of 40 to 49 years. Mainly, the manifestations of the disease were observed on the facial region and limbs. Furthermore, a statistically significant correlation was observed between age groups and the type of leishmaniasis (P > 0.05), as well as between gender and the type of leishmaniasis (P > 0.05). According to the conducted analysis, the prevalence of the disease in Iraq showed a declining trend from 2008 to 2014. This reduction in the disease incidence can be attributed to the improvement in health education status and the adherence to personal hygiene practices among the population